1996
DOI: 10.1002/eji.1830260315
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance is overcome in beef insulin‐transgenic mice by activation of low‐affinity autoreactive T cells

Abstract: To gain insight into the factors controlling the maintenance or loss of T cell self tolerance we produced beef insulin (BI)-transgenic BALB/c mice. Transgenic mice express BI under control of the human insulin promoter and secrete physiological amounts of beef insulin. Although these mice are tolerant to BI, as evidenced by the lack of insulin-specific IgG antibody production following intraperitoneal immunization, tolerance is not complete. Footpad immunization results in a weak antigen-specific T cell prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
27
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 36 publications
4
27
0
Order By: Relevance
“…This probably reflects the in vitro differences in cytolytic activity observed for these CTL, both as populations and as clones, and demonstrates the principle that expression of greater amounts of peripheral Ag results in a more profoundly tolerized repertoire, as reflected in the lower avidity of CTL from InsHA ϩ/ϩ mice. This correlation has been previously observed in the CD4 ϩ T lymphocyte repertoire of transgenic mice expressing either beef insulin (60) or varying levels of hen egg white lysozyme in vivo (61).…”
Section: Discussionsupporting
confidence: 78%
“…This probably reflects the in vitro differences in cytolytic activity observed for these CTL, both as populations and as clones, and demonstrates the principle that expression of greater amounts of peripheral Ag results in a more profoundly tolerized repertoire, as reflected in the lower avidity of CTL from InsHA ϩ/ϩ mice. This correlation has been previously observed in the CD4 ϩ T lymphocyte repertoire of transgenic mice expressing either beef insulin (60) or varying levels of hen egg white lysozyme in vivo (61).…”
Section: Discussionsupporting
confidence: 78%
“…Significantly, they have shown that vaccination of insulin-dependent HA mice can activate these low avidity CTLs that are able to reject tumor cells expressing high levels of HA, without destruction of pancreatic islet ␤ cells expressing moderate levels of HA. Studies with other transgenic mouse models expressing model proteins as self Ags have shown that T cells with specificity for self proteins can be demonstrated within the peripheral T cell pool (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). Often, potentially autoreactive T cells manage to escape deletion by virtue of their lower avidity for self Ag even when the transgene element is present in, or is available to, the thymus (44).…”
Section: Figurementioning
confidence: 99%
“…[7][8][9]. Previous studies have provided evidence that thymocytes bearing TCRs with low avidities for self peptides (10,11), or that express low levels of high avidity autoreactive TCRs (and/or low levels of coreceptor molecules; Refs. 12-15), can evade negative selection presumably because their sensitivity for their cognate self peptide is insufficient to trigger negative selection (16).…”
mentioning
confidence: 99%